Reference values of skeletal muscle area for diagnosis of sarcopenia using chest computed tomography in Asian general population. Issue 2 (15th February 2022) - Moon, Sung Woo; Lee, Sang Hoon; Woo, Ala; Leem, Ah Young; Lee, Su Hwan; Chung, Kyung Soo; Kim, Eun Young; Jung, Ji Ye; Kang, Young Ae; Park, Moo Suk; Kim, Young Sam; Kim, Chang Oh; et al.
Abstract: Background: Diagnostic cutoff points for sarcopenia in chest computed tomography (CT) have not been established although CT is widely used for investigating skeletal muscles. This study aimed to determine reference values for sarcopenia of thoracic skeletal muscles acquired from chest CT scans and to analyse variables related to sarcopenia using the cutoff values determined in a general Asian population. Methods: We retrospectively reviewed chest CT scans of 4470 participants (mean age 54.8 ± 9.9 years, 65.8% male) performed at a check‐up centre in South Korea (January 2016–August 2017). To determine cutoffs, 335 participants aged 19–39 years (mean age 35.2 ± 3.6 years, 75.2% male) were selected as the healthy and younger reference group, and 4135 participants aged ≥40 years (mean age 56.4 ± 8.4 years, 65.1% male) were selected as the study group. We measured the following: cross‐sectional area (CSA) of the pectoralis, intercostalis, paraspinal, serratus, and latissimus muscles at the 4 th vertebral region (T4CSA ); T4CSA divided by height 2 (T4MI); pectoralis muscle area (PMCSA ); and PMCSA divided by height 2 (PMI) at the 4 th vertebral region. Sarcopenia cutoff was defined as sex‐specific values of less than −2 SD below the mean from the reference group. Results: In the reference group, T4CSA, T4MI, PMCSA, and PMI cutoffs for sarcopenia were 100.06cm 2, 33.69cm 2 /m 2, 29.00cm 2, and 10.17cm 2 /m 2 in male, and 66.93cm 2, 26.01cm 2 /m 2, 18.29cm 2, and 7.31cm 2 /m 2 in female, respectively. The prevalence of sarcopenia in the study group measured with T4CSA, T4MI, PMCSA and PMI cutoffs were 11.4%, 8.7%, 8.5%, and 10.1%, respectively. Correlations were observed between appendicular skeletal mass divided by height 2 measured by bioelectrical impedance analysis (BIA) and T4CSA ( r  = 0.82; P  < 0.001)/T4MI ( r  = 0.68; P  < 0.001), and ASM/ height 2 measured by BIA and PMCSA ( r  = 0.72; P  < 0.001)/PMI ( r  = 0.63; P  < 0.001). In the multivariate logistic regression models, sarcopenia defined by T4CSA /T4MI were related to age [odds ratio (95% confidence interval), P ‐values: 1.09 (1.07–1.11), <0.001/1.05 (1.04–1.07), <0.001] and diabetes [1.60 (1.14–2.25), 0.007/1.47 (1.01–2.14), 0.043]. Sarcopenia defined by PMCSA /PMI were related to age [1.09 (1.08–1.10), <0.001/1.05 (1.03–1.06), <0.001], male sex [0.23 (0.18–0.30), <0.001/0.47 (0.32–0.71), <0.001], diabetes [2.30 (1.73–3.05), <0.001/1.63 (1.15–2.32), 0.007], history of cancer [2.51 (1.78–3.55), <0.001/1.61 (1.04–2.48), 0.033], and sufficient physical activity [0.67 (0.50–0.89), 0.007/0.74 (0.56–0.99), 0.042]. Conclusions: The reference cutoff values of a general population reported here will enable sex‐specific standardization of thoracic muscle mass quantification and sarcopenia assessment.